(untitled) (Journal of Asian Development Studies, 2024)
The focus of current study is to discuss the tax compliance structure and the role of administrative reforms in domestic revenue mobilization. There are several reasons why unresolved tax audits keep piling up with (particularly) large taxpayers, causing complaints. After the comprehensive review of existing tax structure, discussion on the existing infrastructure and based on empirical analysis, it is suggested that too much reliance on tax audit revenue, need for a more cooperative future relationship between GDT and large taxpayers, impartial express arbitration of tax disputes to clear the backlog and update the structure of the tax audit system. Lastly, taxpayers need (even3 ) more effectual education so they can comply faster and more accurately: Our research shows that delays at the taxpayer side are just as important, or even more so, than the delays observed at the GDT side. Even large taxpayers have difficulties understanding and preparing necessary documentation (26%) or are unclear about the correct application of laws and regulations (16%). Along the same lines, the GDT should consider to make the incentive for voluntary self-correcting of past tax returns permanent, at least to some degree.